Discourse Function in Wordwall: An Analysis of Instructions and feedback in English Learning Activities - Ulfa Rayhani Nst; Nida Husna; Didin Nuruddin Hidayat (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study examines the discourse functions of instructional language and feedback in a Wordwall-based English language learning exercise. Using qualitative discourse analysis techniques based on Systemic Functional Linguistics (SFL) and Sinclair and Coulthard's classroom discourse model, this research analyzed six publicly worwall activities intended for elementary students. The study identified six primary discourse functions: directive, procedural, evaluative, motivational, corrective, and informative. Directive and procedural functions dominated the instructional phase, providing clarity and task organization, while evaluative and motivational functions defined the feedback phase, providing reinforcement and emotional support. Informational feedback occurred less frequently, suggesting that automatic responses had limited linguistic scaffolding. Overall, Wordwall is not only a gamified learning tool, but also as a structured discourse enviorenment that influences learner engagement,participation,meaning making. These observations provide practical implication for educators,especially in the selection, modification and supplemantion of wordwall activities to optimize instructional clarity, improve feedback clarity and promote reflective and language centered learning.